2016
DOI: 10.1080/13811118.2015.1033122
|View full text |Cite
|
Sign up to set email alerts
|

Suicide Prevention Gatekeeper Training: Can They Advance Prevention in Indian Country?

Abstract: American Indian youth have the highest suicide rates in the United States; however, many do not use services and access barriers exist. This study was a cross-sectional evaluation of 6 gatekeeper trainings conducted on 1 reservation with N = 84 individuals. Analyses examined participant characteristics, impact on training objectives, and satisfaction. The majority of participants were American Indian and female (89.3%). Significant increases in knowledge (p < 0.001) and self-efficacy (p < 0.001) were observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…No measure was found that suited the aims of this study. Rather, we identified several myths commonly believed by lay people [9,13,14,[16][17][18][24][25][26][27] and included seven items in the survey representing these myths: (1) 'There is a risk that asking someone about suicide will make them start thinking about it' [14,16,18]; (2) 'There is a risk of making the situation worse if I try to help someone who is thinking about suicide' [18];…”
Section: Suicide Mythsmentioning
confidence: 99%
See 1 more Smart Citation
“…No measure was found that suited the aims of this study. Rather, we identified several myths commonly believed by lay people [9,13,14,[16][17][18][24][25][26][27] and included seven items in the survey representing these myths: (1) 'There is a risk that asking someone about suicide will make them start thinking about it' [14,16,18]; (2) 'There is a risk of making the situation worse if I try to help someone who is thinking about suicide' [18];…”
Section: Suicide Mythsmentioning
confidence: 99%
“…Adoption of this strategy is based on the assumption that belief in suicide 'myths' can have a negative effect on suicide prevention intentions and behaviors [9,12]. Examples of suicide myths shown to be relatively common among community samples include the belief that people who attempt suicide don't talk about it [13,14]; that suicide happens without warning [15][16][17]; that asking someone about suicide could make them start thinking about it [14,16,18]; and that once a person has made up his or her mind about suicide, no one can stop him or her [14,16]. Such views of suicide may reduce the likelihood of community members intervening with someone who may be at risk because they believe they might make the situation worse or that suicide is not preventable.…”
Section: Introductionmentioning
confidence: 99%
“…Lower levels of satisfaction and poorer outcomes, including a concerning increase in suicidal ideation among First Nations tribal community members in Canada, raises concern about appropriateness of standardized training for minority groups [22]. The issue of culture was raised by other researchers [23,31]. It has been concluded there was insufficient evidence to recommend gatekeeper training for indigenous persons in one systematic review of suicide prevention interventions [40].…”
Section: Discussionmentioning
confidence: 99%
“…On the Fort Apache Indian Reservation in Arizona, American Indians were among participants in ASIST training (n=84) [23]. Positive gains in knowledge, self-efficacy and intent to use were identified, however participants reported training did not address cultural needs [23].…”
Section: Communitiesmentioning
confidence: 99%
“…In most studies, knowledge improvement is a convincing outcome of the gatekeeper training [ 16 , 24 29 ] as well as improved self-efficacy [ 25 , 28 , 30 , 31 ] and confidence to act when in contact with a suicidal person [ 16 , 24 , 27 , 32 ]. Furthermore, gatekeeper training seems beneficial in referring youth to appropriate services, especially within school-based settings [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%